Optimization of the iot network protocol choozing for monitoring audio information - U. A. Vishnyakou; Bahaa Shaya (Системный анализ и прикладная информатика)
The subject of research is the choice of a protocol in the Internet of Things (IoT) network for monitoring and analyzing audio information. The purpose of the article is to optimize the process of choosing a protocol for monitoring audio information based on IoT and evaluate the results. The authors have developed an IoT framework for monitoring and analyzing audio and voice information. The IoT network includes a sound sensor (microphone), a unit for analyzing the information received from it and a decision-making module. The description of protocols in the IoT network for assessing the sound level is given: the Wireless USB standard, the narrowband standard of the NB-IoT.The hierarchy analysis method was used to select the best protocol. The methodology and its main formulas for calculating the best option are given. A table of the four selected protocols for the IB network is given. As characteristics of the protocols, the following are considered: downlink speed, latency, device bandwidth, device transmission power. A matrix of paired comparisons of protocol parameter indicators based on expert assessments has been formed. Four matrices of paired comparisons of transmission standards variants in relation to the indicator of speed, delay, bandwidth of devices, transmission power of devices are constructed. Calculations of local vectors and priority vectors of quality indicators were performed for these four matrices. Then the matrix of vectors of global priorities is calculated by calculating the sum of the products of local vectors of matrices of paired comparisons of transmission standards variants on the corresponding priority vectors of quality indicators of the matrix of paired comparisons of protocol parameters. From the results obtained, the best protocol option for the network and sound monitoring was determined by the maximum value.